2013
DOI: 10.1590/s0004-27302013000600010
|View full text |Cite
|
Sign up to set email alerts
|

Iodine nutrition in elementary state schools of Queretaro, Mexico: correlations between urinary iodine concentration with global nutrition status and social gap index

Abstract: OBJECTIVE AND METHODS: To estimate median urinary iodine concentration (UIC), and to correlate it with global nutrition indicators and social gap index (SGI) in 50 elementary state schools from 10 municipalities in the State of Queretaro, Mexico. RESULTS: 1,544 students were enrolled and an above of requirements of iodine intake was found (median UIC of 297 µg/L). Iodine status was found as deficient, adequate, more than adequate and excessive in 2, 4, 19 and 25 schools, respectively. Seventy seven percent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
2
10
3
Order By: Relevance
“…This is contrary to the hypothesis of García-Solis et al (15), who suggested that a high consumption of snack foods rich in energy and iodized salt could be the etiology of the positive correlation found between UIC and BMI (r = 0.47; p < 0.005), and overweight/obesity (r = 0.41; p < 0.05) in their 2013 Mexican study.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…This is contrary to the hypothesis of García-Solis et al (15), who suggested that a high consumption of snack foods rich in energy and iodized salt could be the etiology of the positive correlation found between UIC and BMI (r = 0.47; p < 0.005), and overweight/obesity (r = 0.41; p < 0.05) in their 2013 Mexican study.…”
Section: Discussioncontrasting
confidence: 78%
“…However, three countries-Chile, Ecuador, and Brazil-are now considered at risk for iodine excess, along with its adverse health consequences (1). Recently, a Mexican study evaluating ID and excessive iodine intake (EII) in children from state elementary schools found both a positive correlation between urinary iodine concentration (UIC) values and the prevalence of overweight/obesity, and a significant negative correlation between UIC and index of social development (15). However, this study was not able to clarify the association between poverty and ID completely, since only 4% of schools had insufficient iodine intake, and half of them were living in municipalities with a higher social development index (15).…”
Section: Introductionmentioning
confidence: 99%
“…-In a recent study, a positive correlation between urinary iodine concentration and overweight and obesity was revealed in schoolchildren (23) and could be explained by the availability and consumption of snack food rich in energy and iodized salt (23). In our study group, the difference between the percentage of schoolchildren with obesity or overweight in the subgroups from Bucharest (13.88%) and Sibiu (16.66%) was not statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
“…This data confirming that iodine deficiency is associated with hypertensive disease. In Mexico, the lack of nutritional information, as well as water contamination with heavy metals and consumption of foods rich in goitrous substances or junk foods, may be contributing to iodine deficiency in vulnerable groups such as children and pregnant women (30)(31)(32). However, further studies are required to determine the source of iodine deficiency in vulnerable groups, pregnant women and children specifically.…”
Section: Discussionmentioning
confidence: 99%